Campus urbanism in peripheral cities: Enhancing social engagement and sustainable investment in Hail University, Saudi Arabia - Alnaim, Mohammed Mashary; Alshenaifi, Mohammad; Noaime, Emad; Albaqawy, Ghazy; Abuhussain, Mohammed Awad; Abdelhafez, Mohamed Hssan Hassan (Frontiers in Built Environment, 2025)
IntroductionThis study investigates the evolving role of university campuses in driving urban and social development, with a specific focus on Hail University in Saudi Arabia. It explores how peripheral higher education institutions can act as urban anchors that stimulate economic growth, community integration, and spatial regeneration. Particular emphasis is placed on the latent potential of campus-adjacent commercial structures—such as a hotel and shopping center—to contribute to urban sustainability and social engagement.MethodsThe research employed a mixed-methods approach, conducted during the academic year 2022–2023. Data were collected from 1,460 participants, including 292 members of the local community and 1,168 university-affiliated individuals (students, faculty, and staff). Methods included direct observational fieldwork, two structured online surveys, and semi-structured interviews. The study examined perceptions across four key dimensions: urban management, space engagement, social activities, and investment opportunities.ResultsFindings reveal a pronounced spatial disconnection between the university and the surrounding urban fabric, contributing to underutilization of the hotel and shopping center and limiting campus vibrancy. While stakeholders expressed interest in social engagement and improved facilities, physical isolation, weak internal connectivity, and a lack of cultural integration were cited as barriers. Statistical analysis confirmed significant variation in perceptions across stakeholder groups, and thematic coding of interviews revealed four dominant concerns: disconnection, asset underuse, cultural invisibility, and latent mixed-use potential.Discussion and ConclusionsThe study concludes with strategic recommendations to reposition peripheral university campuses as sustainable urban anchors. It proposes design, policy, and governance interventions to improve campus connectivity, activate underused commercial assets, and embed universities more effectively within local development agendas. The research contributes a conceptual model—Peripheral Campus Urban Anchoring—which may inform urban development strategies in similarly situated universities across the region, supporting Saudi Arabia’s broader Vision 2030 goals.